Non-invasive parameters for the detection of variceal bleed in patients of liver cirrhosis, an experience of a tertiary care hospital in Pakistan - Umar, Anam; Qazi, Fakhar Ali; Sattar, Rukhsana Abdul; Umar, Beena (Asian Journal of Medical Sciences, 2014)
Objective: Cirrhotic patients commonly undergo screening endoscopy for the existence of esophageal varices. The use of this invasive procedure which is expensive, poorly tolerable and generally not acceptable for the patients is increasing due to increasing number of patients with chronic liver disease and their enriched survival. In this study, our aim is to identify clinical, biochemical, and ultrasonography parameters which might non-invasively predict the presence of esophageal varices and risk of bleeding in patients with liver cirrhosis. Material and Methods: Total 150 Patientsof chronic liver disease admitted in ward-5, JPMC(Sep 2011-Feb 2012) with a complaint of hematemesis or melena were included in the study. Platelet counts of 75,000 to 150,000/μL was defined as grade 1 thrombocytopenia, 50,000 to <75,000/μL as grade II, 25,000 to <50,000/μL as grade III and below 25,000/μL as grade IV. The normal range for the INR is 0.8–1.2. Portal vein size of 1.2 cm or above was taken as dilated. Spleen of >13 cm was considered as enlarged in our study. Results: Out of 72 patients of variceal bleed 69 (46%) were males and 81(54%) were females. Thrombocytopenia was present in 64 (88%) patients with mean platelet count of 85.86/μL (±69.79). Deranged coagulation profile was present in 56 (77%) cases with mean INR of 1.63 (±0.5). Portal vein diameter (PVD) of >1.2 cm was found in 46(63.8%) of patients with mean PVD of 1.22(±0.3023) and splenic size of >13 cm was reported in 54 (75%) cases with mean splenic diameter of 14.5 cm (±2.39). Conclusion: Thrombocytopenia, deranged coagulation profile, large splenic size, and dilated portal vein strongly predict the risk of variceal bleeding. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9624 Asian Journal of Medical Sciences Vol.6(1) 2015 61-66